2014
DOI: 10.1016/j.ijmultiphaseflow.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A PIV investigation of stratified gas–liquid flow in a horizontal pipe

Abstract: Simultaneous Particle Image Velocimetry (PIV) measurements of stratified turbulent air/water flow in a horizontal pipe have been performed using water droplets as tracers in the gas-phase. The use of water droplets as tracers ensures that the water surface tension remains unaffected and thus allows small scale interfacial structures, such as capillary waves to occur naturally. Experiments have been conducted in a 31 m long, 100 mm diameter PVC pipe using air (density 1.20 kg/m 3 and viscosity 18.4 µPa•s) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 34 publications
7
49
0
Order By: Relevance
“…The data under investigation was acquired during an experimental campaign conducted at the Hydrodynamic Laboratory at the University of Oslo. The experimental techniques PIV, conductance probing and hot-wire anemometry were combined to study of air-water flow in pipes (Ayati et al, 2014(Ayati et al, , 2015(Ayati et al, , 2016. In this paper, we will only focus on the data stemming from the wave gauge, i.e.…”
Section: Experimental Set-up and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The data under investigation was acquired during an experimental campaign conducted at the Hydrodynamic Laboratory at the University of Oslo. The experimental techniques PIV, conductance probing and hot-wire anemometry were combined to study of air-water flow in pipes (Ayati et al, 2014(Ayati et al, , 2015(Ayati et al, , 2016. In this paper, we will only focus on the data stemming from the wave gauge, i.e.…”
Section: Experimental Set-up and Methodologymentioning
confidence: 99%
“…Nevertheless, the next generation of flow simulators are expected to include "regime-capturing" approaches which rely on finer grid resolution (Issa & Kempf, 2003;Carneiro et al, 2011;Danielson et al, 2012;Nieckele et al, 2011;Nieckele & Carneiro, 2017). Furthermore, recent developments in experimental investigation of this system (Birvalski et al, 2014(Birvalski et al, , 2015(Birvalski et al, , 2016Ayati et al, 2014Ayati et al, , 2015Ayati et al, , 2016Ayati et al, , 2017André & Bardet, 2017), have shown that the overall bulkflow is strongly coupled with wavy interface. To this end, detailed description of measured interfacial waves is expected to be of valuable use with respect to validation of models and CFD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The first to apply PIV in gas-liquid pipe flow were Vestøl & Melaaen (2007). Recently, Ayati et al (2014) also applied PIV in both phases of the flow, and resolved the air-water interface. Both studies are, however, of limited scope and reported difficulties in obtaining measurements in some parts of the flow due to light reflections on the interface or the pipe wall.…”
Section: Introductionmentioning
confidence: 99%
“…A range of different measurement techniques e.g. conductance probes (Strand, 1993), PIV (Ayati et al (2014), Ayati et al (2015)), hot wire measurements (Ayati et al, 2016) and optical investigation Sanchis et al (2011) have been utilized to establish physical parameters such wave amplitude, wave spectra, and velocities in both liquid and gas phase Ayati et al (2015).…”
Section: Multiphase Pipe Flowmentioning
confidence: 99%